Extractive desulphurization of model oil using sulphonium based ionic liquids - Lethesh, K.C. (Trans Tech Publications Ltd, 2014)
Synthesis of a novel class of cyclic sulphonium based ionic liquids was performed. The ionic liquids were characterized using1H NMR spectroscopy, FTIR spectroscopy and CHNS elemental analysis. The physicochemical properties of the ionic liquids such as density viscosity and thermal decomposition temperature of the synthesized ionic liquids were determined. The potential of these ionic liquids for the extractive desulphurization of model oil was investigated. Â© 2014 Trans Tech Publications, Switzerland.